Assessing donor kidney function: the role of CIRBP in predicting delayed graft function post-transplant - Leng, Qianghua; Ma, Maolin; Tang, Zuofu; Jiang, Weichen; Han, Fei; Huang, Zhengyu (Frontiers in Immunology, 2025)
IntroductionDelayed graft function (DGF) shortens the survival time of transplanted kidneys and increases the risk of rejection. Current methods are inadequate in predicting DGF. More precise tools are required to assess kidney suitability for transplantation. Cold-inducible RNA-binding protein (CIRBP) expression has been linked to acute kidney injury, suggesting its potential as a new biomarker for transplanted kidney function.MethodsWe included deceased donors and recipients who had undergone successful kidney transplantation between 2016 and 2019. Recipients and their paired donors are assigned to either the DGF or immediate graft function (IGF) group, based on the recipient’s recovery of graft renal function. Donor plasma CIRBP levels were measured using an enzyme-linked immunosorbent assay kit to assess their relationships with DGF.ResultsDonor plasma CIRBP concentrations in the DGF group were approximately twice as high as those in the IGF group (6.82 vs. 3.44; P<0.001). DGF occurred in all cases where CIRBP concentrations exceeded 7.92 ng/mL. Furthermore, univariate and multivariate analyses (odds ratio [OR]=1.660; P<0.001) confirmed that donor plasma CIRBP level was an independent risk factor for DGF. Additionally, higher CIRBP levels were associated with increased plasma creatinine at 6 months (R²=0.08; P<0.001), and survival analysis showed shorter kidney survival in recipients with DGF (P=0.002).ConclusionsThis study demonstrated that donor plasma CIRBP levels can effectively predict the occurrence of DGF. CIRBP is a potential novel biomarker for evaluating transplanted kidney function.Clinical trial registrationhttps://clinicaltrials.gov, identifier NCT06641622.